Assessment of Mesiodistal Angulations of Mandibular Canine and Posterior Teeth using Orthopantomogram - Gautam, Utsav; Shrestha, Rabindra Man; Dhakal, Jyoti (Orthodontic Journal of Nepal, 2024)
Background: Appropriate mesiodistal angulation of teeth is necessary for the stability of the stomatognathic system, so achieving proper angulation should be included in the orthodontic treatment objectives. The commonly used panoramic radiograph can be utilized for the assessment of mesiodistal angulation of teeth. Aims and Objective: To evaluate and compare mesiodistal angulations of mandibular canine and posterior teeth with and without third molar. To compare mesiodistal angulation between the sides with and without third molar. Material and methods: This is a cross-sectional comparative study using an orthopantomogram (OPG) of 66 subjects aged 17-29 years. The sample was divided into: with third molar and without third molar groups. A reference line was used to determine the angulations of teeth that passed through the mental foramen. The kappa statistic test was done to determine the intra-observer variability. Student’s t-test was performed to compare the mesiodistal angulations of mandibular canine and posterior teeth with and without a third molar. Result: There were a significant difference in mesiodistal angulations between the second molar (p=0.00), and first molar (p=0.00) on the right side, and second molar (p=0.00), first molar (p=0.005), second premolar (p=0.01) and first premolar (p=0.04) on the left side. There was also a difference in mesiodistal angulation for the first molar (p=0.05) between the right and left side when the third molar was present. Likewise, there was a difference in mesiodistal angulation for the second molar (p=0.016) between right and left side when the third molar was absent. Conclusion: The presence of a third molar significantly affected mesiodistal angulation of molars and premolars while angulation of canine was not affected.